School-based high-intensity interval exercise program in children with overweight induce a greater improvements in body composition and physical fitness than moderate-intensity continuous exercise - Chongwen Zuo; Xiaoyan Ma; Yuan Yang; Yupeng Cui; Chaoqun Ye (BMC, 2023)
Abstract Background High-intensity interval running exercise (HIIE) is emerging as a time-efficient exercise modality for improving body composition and fitness in comparison with moderate-intensity continuous aerobic exercise (MICE); however, existing evidence is still unclear in children with overweight and thus we compared the effects of HIIE and MICE on body composition, muscular, and cardiorespiratory fitness in children with overweight. Methods In this randomized study, 40 male children with overweight aged 7-10 years were divided into an 8-week exercise regime: (1) HIIE group [n = 20; 2 sets of 15 × 20s at 85-95% maximal aerobic speed (MAS) separated by 15 × 20s recovery at 50% MAS, 3 days per week] and (2) MICE group [n = 20; 30 min at 60-70% MAS, 3 days per week]. Body composition, muscular and cardiorespiratory fitness were assessed before and after the 8-week intervention at similar times and conditions of the day. Results Following the 8-week HIIE protocol, weight, BMI, and fat mass decreased significantly (weight: − 1.4% vs. 0.2%, p < 0.05; BMI: − 3.1% vs. − 0.7%, p < 0.05; fat mass: − 7.7% vs. − 1.6%, p < 0.01) as compared with MICE; while the VO2peak and MAS increased significantly in both groups, the increase in HIIE group was significantly greater than that of MICE group (VO2peak: 10.3% vs. 3.5%, p < 0.01; MAS:7.7% vs. 4.5%, p < 0.05). Although significant improvements in muscular fitness were observed in HIIE and MICE groups [counter movement jump (CMJ): 7.8% vs. 5.4%; sprinting ability: − 3.7% vs. − 1.7%], no significant differences were seen between them (p > 0.05). Conclusion Our findings suggested that school-based HIIE intervention was highly in improving body composition and cardiorespiratory fitness of children with overweight than the MICE regime; however, MICE still provided improvements over time that were just not to the same magnitude of HIIE.